4(y+1)=-6

Simple and best practice solution for 4(y+1)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y+1)=-6 equation:


Simplifying
4(y + 1) = -6

Reorder the terms:
4(1 + y) = -6
(1 * 4 + y * 4) = -6
(4 + 4y) = -6

Solving
4 + 4y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 4y = -6 + -4

Combine like terms: 4 + -4 = 0
0 + 4y = -6 + -4
4y = -6 + -4

Combine like terms: -6 + -4 = -10
4y = -10

Divide each side by '4'.
y = -2.5

Simplifying
y = -2.5

See similar equations:

| x^2-2x+10=y | | 5x+2x-5=44 | | 7t^3-21t^2-2926t=0 | | 9+5x=4x+12 | | -4+5w=-14 | | 8x+9x-52=104-9x | | -(x-8)=3(-3x+4) | | 8=Xsquared-5x+8 | | 120+30m=80+50m | | 5-x=18+3x | | 4+2.5x=6.5x+2 | | -1+3-x=4+2x | | 28.75=6g+3.97 | | -6(2n-1)=-66 | | a+4+4a=14 | | 2g+16=2g+28 | | 8g=4+10g | | 1/2+(2/3+3/4)-4/5*5/6= | | 3(v+8)-5v=6 | | .25x+9.99=113.74 | | 5(y-1)=2(y-4)-6 | | 9y-6x=3+5x | | 7s-(3s+1)=4(s+s) | | -2(n-5)+4n=17 | | -(-x+w)-2(-4w+5x)= | | F(x)=4x+10F(2) | | sqrt(3x+1)-sqrt(x-1)=2 | | 4a+3=7a-16 | | 80=11c+32 | | 1/2+(2/3/3/4)-4/5*5/6= | | 4y-8-3y=2y-12 | | 8x+7=12-2x |

Equations solver categories